Plagiocephaly Perception and Prevention: A Need to Intervene Early to Educate Parents - Sonja Burmeister; Allison N. Kayne; Ali R. Yazdanyar; J. Nathan Hagstrom; David B. Burmeister (Scholarworks @ WMU, 2021)
Background: Plagiocephaly is a condition where the cranium has been malformed because of external forces or premature cranial suture fusion. This study's objective was to gather and examine data regarding parent and caregiver awareness of plagiocephaly and its potential impact on development as well as to determine their rate of concern for positional flattening. Method: A cross-sectional survey study was conducted. Categorical variables were described by frequency and proportions. The study was conducted across eight outpatient pediatric sites. Approximately 1,100 parents and caregivers were targeted. Inclusion criteria required participants to be willing to answer the questionnaire, to be 18 years of age or older, and to have an infant 12 months of age or younger. Results: There were 404 participants, most of whom were female (89.8%) and 30-39 years of age (61.1%). Nineteen children (4.7%) were reported to have plagiocephaly, torticollis, and/or muscle weakness (PTM). A greater percentage of the participants with a child with PTM knew of positional flattening or plagiocephaly (73.3%) compared to those without (53.8%). The respondents with a child with PTM had a greater concern about plagiocephaly than those without (p = .03). Many of the respondents (65.3%) would use a device designed to prevent plagiocephaly. Conclusion: Many parents and caregivers were unaware of plagiocephaly and its potential impact on facial symmetry. A greater percentage of the participants with a child with PTM knew of positional flattening and also had a greater concern about plagiocephaly than those without.